Development of a biomimetic sensor for selective identification of cyanide. Issue 33 (10th August 2016) - Figueira, E. C.; Neres, L. C. S.; Ruy, M. R. S.; Troiano, G. F.; Sotomayor, M. D. P. T.
Abstract : A biomimetic sensor is proposed as a promising new analytical method for the determination of cyanide in different samples. Abstract : A biomimetic sensor is proposed as a promising new analytical method for the determination of cyanide in different samples. The sensor was prepared by modifying a carbon paste electrode cobalt II 1, 2, 3, 4, 8, 9, 10, 11, 15, 16, 17, 18, 22, 23, 24, 25-hexadecafluoro-29 H, 31 H -phthalocyanine complex [CoPc]. The measurements were carried out using cyclic voltammetry (CV) and square wave voltammetry (SWV) for electrochemical characterization and quantification purposes, respectively. SWV measurements carried out vs. Ag/AgCl(KClsat ), using a 0.5 mol L −1 NaOH solution at pH 12.0 as the support electrolyte, provided the best responses, with a linear range of 2.4 × 10 −5 to 1.7 × 10 −4 mol L −1 and limits of detection and quantification of 3.6 × 10 −6 and 1.2 × 10 −5 mol L −1, respectively. A detailed investigation of the sensor selectivity, employing eleven different ions, was also performed. Recovery studies were carried out using river and drinking water samples and the results obtained demonstrated that it is a reliable alternative method for the detection of this analyte.